China. A market that Colombia must strengthen with the Pacific Alliance (2013)
China is in a period of productive transformation and is moving towards high value-added industries as its main sources of production, parallel basing the economy on the domestic consumption of the country and reducing its dependence on exports of basic manufacturing. The current situation in the European Union (the largest trading partner of China) and the United States has outlined that the economic growth of the People's Republic of China until 2015 is projected between 8% and 9% (McKinsey 2012, Boston Consulting Group 2012) , growth reduced mainly by the decline in exports, the increase in labor and oil prices worldwide. Thus, the Chinese Government has chosen to focus much of the efforts of economic growth on domestic consumption, directed mainly by the growing middle class in the country and development in the interior and west of China. This represents countless commercial opportunities for food and product export economies with a certain degree of transformation, which in the case of member countries of the Pacific Alliance (except Colombia) are taking advantage of these trends and strengthening their presence in the market with the largest number of consumers worldwide. Peru, Chile and Mexico are already on a path traveled in commercial matters, the Pacific Alliance becomes a field of learning and potential takeoff for Colombia in taking advantage of the high demand of the Chinese market.